GENDER AND RETURNS TO MARKETING OF NON-TIMBER FOREST PRODUCTS IN SOUTHWEST NIGERIA (2017)
Marketing of commercially important Non-timber Forest Products (NTFPs) can be a potential source of livelihoods and a major source of rural income for both men and women. Many of these NTFPs have market demand, so they offer an opportunity to earn cash income especially in cash-constrained rural economies where alternative sources of cash-income generating employments arc very limited. The study assessed gender and returns to non-timber forest products marketing in Omo Forest Reserve in Ogun State. Data was obtained from 192 respondents through a multistage sampling process to select four villages each of the four administrative areas (JI, J3, J4 and J6) of the forest reserve. Results showed that a majority of the respondents were female with a mean age of 4 7±9 .41 years and an average household size of7±3.22 members. A typical household had an average mean dependency ratio of 1.1±0.83. About 83.3% of the respondents had at least primary education and there was a significant difference in the means of total cost, gross margin, profit and marketing efficiency from marketing ofNTFPs among the male and female extractors. High transaction cost was the most severe constraint faced during the collection of NTFPs. Marketing of these NTFPs was profitable and highly efficient.